Informed consent of human subjects: a review - Islam, Mohammad Rashedul (Bangladesh Journal of Bioethics, 2014)
Informed consent is a vital part of the research process, and as such entails more than obtaining a signature on the consent form. Researchers or investigators must educate potential subjects to ensure that they can reach a truly informed decision about whether or not to participate in the research. Their consent must be given freely, without coercion, and must be based on a clear understanding of what participation involves. Only then it can be regarded as informed consent. Although a relatively recent phenomenon, the role of informed consent in human research is central to its ethical regulation and conduct. However, guidelines often recommend procedures for obtaining informed consent (usually written consent) that are difficult to implement in developing countries. This paper reviews the guidelines for obtaining informed consent and also discusses prevailing views on current controversies, ambiguities and problems with these guidelines and suggests potential solutions. DOI: http://dx.doi.org/10.3329/bioethics.v5i1.18444 Bangladesh Journal of Bioethics 2014 Vol.5(1): 20-35